(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Medium scale biomass temperature control is a specific field of control issues where one of the most important features is cost effectiveness. It means that any kind of control system improvement should be done with the lowest possible additional costs. Generally, the basic control of such kind of boiler regulates temperature of outlet heating water. This control can be also performed by a conventional or advanced control. Although the main problem of this study is the construction of the model of biomass boiler for control purposes, our task deals with technology of boilers and principles of its inner processes as well. Creation of the model comes out not only from these important findings, but also from experimental data collected during measurements in real operation. Heat and mass balance calculations were made according to these data and they serve to precise dynamic properties of experimental unit for biomass combustion. Based on the derived mathematical model of the biomass boiler, here is possibility to enhance the control by additional algorithms that are responsible for extended optimization functions. In this paper, an advanced process control such as sliding mode control system (SMC) is used to control the temperature of the boiler water. The results show that SMC has strong immunity for the disturbance and the varying of process parameters.